Immune Thrombocytopenia and JAK2V617F Positive Essential Thrombocythemia: Literature Review and Case Report - M. A. Sobas; T. Wróbel; K. Zduniak; M. Podolak-Dawidziak; J. Rybka; M. Biedroń; M. Sawicki; J. Dybko; K. Kuliczkowski (Case Reports in Hematology)
We present the case where immune thrombocytopenia (ITP) and essential thrombocythemia (ET) sequentially appeared in the space of twenty-one years of follow-up. Impaired platelet production is present in both diseases, but clinical presentation and treatment are different. On the basis of this case history a possible role of autoimmunity as a predisposing factor to myeloproliferation has been discussed.